Evaluation of Free-Surface Exposure Effects on Tidal Turbine Performance Using CFD - Gyeongseo Min; Wooseok Choi; Haechan Yun; Younguk Do; Kangmin Kim; Weichao Shi; Saishuai Dai; Daejeong Kim; Soonseok Song (Journal of Marine Science and Engineering, 2025)
Tidal turbines represent a promising renewable energy source, generating power from ocean currents. However, due to tidal range variations, they sometimes become partially exposed to the free surface. When this occurs, the turbine experiences reduced power generation and unsteady torque caused by the asymmetric flow. Such conditions can lead to long-term degradation of turbine performance and reliability. From this perspective, a key question arises regarding how significantly power generation differs when turbines are exposed to the free surface. This study was conducted with the objective of quantitatively evaluating the differences in power generation and torque acting on the turbine due to free-surface exposure, in order to address this question. Numerical simulations considering free-surface exposure effects were developed to quantitatively assess these phenomena through Computational Fluid Dynamics (CFD). Additionally, this numerical model was validated by comparison against experimental data and verified by convergence tests. The results revealed that the tidal turbine exhibited power generation differences ranging from a maximum of 45% to a minimum of 0.44%, depending on the degree of free-surface exposure. These findings are expected to serve as valuable indicators for power generation when operating tidal turbines.